COMPARING SHORTTERM SURVIVAL BY ISS AND NISS IN ROAD TRAFFIC ACCIDENTS (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
Accident is an event, independent of human will power, caused by an external force that acts rapidly and results in bodily or mental damage. An accident that takes place on the road involving a vehicle in termed as road traffic accident. India, the former USSR and the USA have reported largest number of traffic related fatalities among all nations. Delhi the 3rd most populous city in  India has the distinction of having 2nd highest ratio of death by accidents among the metropolitan cities of this country. The importance of survival period of any trauma victim cannot be over emphasised. Different methods have been employed to measure the extent of trauma in numerical terms. Among the anatomical scoring systems the most popular method is injury severity score (ISS). It was modified recently in 1997 to new injury severity score (NISS). Both ISS & NISS were correlated to  survival period by multiple regressions among 110 individuals died due to road traffic accidents in East Delhi during 1999-2000.  On comparing both scoring systems it was found that although linear regression does not exit between survival period and them, however NISS correlates better to survival period than ISS.
Keywords: Accident; ISS; NISS; Survival period